Identification and Priority Analysis of Leading Non-Extractive Economic Potentials in Bontang City - A. Faroby Falatehan; Feryanto; Yogi Octavian Murdiono Putra (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Bontang City’s economy is dominated by non-renewable extractive industries, which contribute over 70% of regional GDP and create structural vulnerability and fiscal dependence on revenue-sharing funds. This study aims to identify alternative leading potentials and determine development priorities beyond extractive sectors to support sustainable, renewable-based economic resilience. The novelty lies in integrating sectoral analysis using Location Quotient (LQ) with product-level prioritization through the Rank Order Centroid (ROC) method, supported by regional industrial planning documents. A mixed-methods approach is applied, using secondary data on GRDP at constant prices (2015–2024) and industrial plans, combined with primary data from questionnaires administered to 41 triple helix stakeholders. The findings indicate that the Manufacturing Industry (LQ 2.193) and Corporate Services (LQ 1.492) are the leading sectors based on the LQ analysis. Within the manufacturing industry, eleven alternative superior potentials based on renewable resources have been identified, and based on the ROC analysis, processed fishery and marine products (preference value: 136.871) emerged as a top development priority. These findings provide an evidence-based framework for reducing dependence on the extractive sector and strengthening sustainable regional economic resilience.